Exploring the Links Between Farmers’ Intention to Apply for Rural Development Program and Networks - Stojcheska, Aleksandra Martinovska; Kotevska, Ana; Tuna, Emelj; Simonovska, Ana (Springer International Publishing, 2020)
The rural areas in North Macedonia encompass around half of the territory and population in the country, where agriculture is core activity and source of income, with lack of other employment opportunities. The rural development program (RDP) budget is not fully utilized. Informal networks among rural population are still the most valuable source of social capital and information exchange, whereas formal networks, such as associations or cooperatives, are still lacking to ensure their sustainable and functional role. This paper explores the factors influencing farmers’ intention to apply for RDP, with an emphasis on network membership. The Theory of Planned Behavior and Social Capital Theory are used as framework. A direct survey on 296 family farms was carried out in 2014. The study is conducted using multivariate statistics, structural equation modelling and social network analysis. The model explains farmers’ mid-term intention to use RDP. Farmers’ attitudes and perceived behavioral controls, as well as network activity and participation, significantly influence the intention to apply for RDP funds. Network participation, as well as education levels and investment tendency are positively related to the intention to use RDP. These findings could be reflected in appropriate measures to encourage farmers’ participation in institutionalized networks, thus in addition to their primary aim, to increase the RDP effectiveness as means of providing better opportunities and quality of life in rural areas.
Keywords: North Macedonia Social Capital Theory Theory of planned behaviour